TAFSIR TEMATIK TENTANG KAFA’AH (KESEPADANAN) DALAM PERKAWINAN: ANALISIS HUKUM KELUARGA PERSPEKTIF AL-QUR’AN - Wendi Taufik; Ali Khosim; Athoillah Athoillah (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study examines the Qur’anic perspective on the protection of children and women within Islamic family law through a thematic interpretation approach (tafsīr mawdhū‘ī). Focusing on QS. an-Nisā’ [4]: 2–10 in relation to QS. al-Isrā’ [17]: 31 and QS. al-An‘ām [6]: 151, the research analyzes the linguistic meanings of legal verses (āyāt aḥkām) and their normative implications. The findings show that the Qur’an establishes firm legal and moral obligations to safeguard the rights of vulnerable groups, particularly orphans and women, through principles of justice, compassion, and responsibility. These verses emphasize the protection of life, property, dignity, and fair treatment in family relations, while strongly condemning exploitation and oppression. The study further demonstrates that Islamic family law is not merely a rigid normative system, but a framework oriented toward social justice and human dignity, reflecting the universal principle of raḥmatan lil ‘ālamīn. Through thematic interpretation, the Qur’anic message emerges as coherent and integrative, offering a relevant ethical foundation for the development of contemporary Islamic family law that prioritizes protection, balance of rights and obligations, and social harmony.